Structural, spectroscopic and anion binding properties of 5,10-porphodimethenes, an unusual class of calixphyrins - GIORDANI, SILVIA; SENGE, MATHIAS (My University, 2010)
Complete spectroscopic, structural and anion binding properties are reported for a special class of calixphyrins, namely 5,10-disubstituted porphodimethenes (PDMs). The crystal structure clearly shows that PDMs exhibit nonplanar (distorted) structures with both sp2- and sp3-hybridized meso carbon centres. We were able to obtain and characterize the diacid form [H4(PDM)[[X]2 upon addition of several acids to PDMs, where X denotes anions of different acids: HCl; HBr; MeSO3H; CF3CO2H and HClO4. We found that the PDM dications generated were more conjugated and thus more stable than their corresponding porphyrins. Their potential to coordinate anions was clearly shown using 1H NMR spectroscopy. In addition, we found that when HClO4 was used to protonate PDMs the conversion occurs through an intermediate species, which has been assigned to the elusive monoacid derivative on the basis of UV-vis and 1H NMR experiments.
PUBLISHED
Keywords: porphyrins